Bond Behavior and Interaction Mechanism Between Metal Ce-Fe - Kai ZHANG; Chang-shui WANG (He huaxue yu fangshe huaxue)
By using vacuum distillation to refine and purify metals, some escaped metals may deposit on the inner walls of vacuum chambers and pipelines. In order to effectively remove residual metals, it is necessary to clarify the bonding behavior and mechanism between metals, providing important theoretical basis for the screening of subsequent metal wiping aids. This study focuses on cerium(Ce) metal and analyzes the micro-structure, density, and deposition morphology of Ce metal on the surface of stainless steel. Scanning electron microscopy(SEM) and energy dispersive X-ray spectroscopy(EDS) were used to characterize the morphology and elemental composition of Ce metal deposition on the surface of stainless steel 316L. Based on density functional theory, first principles calculations were performed using VASP program to investigate polyhedral voids in the crystal structure. The structures with different doping levels of Ce metal and Fe metal planes were obtained, and the energy of different doping structures was obtained. The interaction mechanism between Ce metal layer and stainless steel 316L was explored, and the bonding mechanism between Ce metal and stainless steel substrate was obtained by theoretical calculations. In the initial stage, as Ce is transported to the substrate surface, these atoms form tiny, mobile atomic clusters on the substrate, also known as “islands” or “nuclei”. Temperature is a key factor in the formation of an alloy layer between Ce and stainless steel substrate, and high temperatures can easily promote the mutual diffusion between Ce elements and surface elements of stainless steel. As Ce is transported to the surface of the substrate, Ce grains begin to nucleate and grow on the surface of the stainless steel. Subsequently, under the influence of concentration gradient and thermal gradient diffusion, diffusion channels were formed on the surface of the substrate, and Ce atoms gradually diffused from the surface into the interior of the substrate. At the same time, due to the smaller atomic radius and higher diffusion rate of Fe element, it begins to diffuse outward from the matrix and react with Ce atoms at the interface, forming CeFe2 phase. The crystal structure of cerium metal was studied, and the polyhedral voids in the crystal structure were analyzed. By calculating possible metal inter-metallic compounds and different Ce-Fe doping structures in the phase diagram, the stability of various crystal structures was explored. Through theoretical calculations, the bonding mechanism between Ce and Fe is analyzed, indicating that metal bonds are formed between Ce and Fe, and the bonding between Ce and Fe forms various metal inter-metallic compounds such as CeFe5, CeFe2, Ce2Fe17.